SUMO-Dependent Synergism Involving Heat Shock Transcription Factors with Functions Linked to Seed Longevity and Desiccation Tolerance - Carranco, Raúl; Prieto-Dapena, Pilar; Almoguera, Concepción; Jordano, Juan (Frontiers in Plant Science, 2017)
A transcriptional synergism between HaHSFA9 (A9) and HaHSFA4a (A4a) contributes to determining longevity and desiccation tolerance of sunflower (Helianthus annuus, L.) seeds. Potential lysine SUMOylation sites were identified in A9 and A4a and mutated to arginine. We show that A9 is SUMOylated in planta at K38. Although we did not directly detect SUMOylated A4a in planta, we provide indirect evidence from transient expression experiments indicating that A4a is SUMOylated at K172. Different combinations of wild type and SUMOylation site mutants of A9 and A4a were analyzed by transient expression in sunflower embryos and leaves. Although most of the precedents in literature link SUMOylation with repression, the A9 and A4a synergism was fully abolished when the mutant forms for both factors were combined. However, the combination of mutant forms of A9 and A4a did not affect the nuclear retention of A4a by A9; therefore the analyzed mutations would affect the synergism after the mutual interaction and nuclear co-localization of A9 and A4a. Our results suggest a role for HSF SUMOylation during late, zygotic, embryogenesis. The SUMOylation of A9 (or A4a) would allow a crucial, synergic, transcriptional effect that occurs in maturing sunflower seeds.